Calculation of environmental flows within the major tributaries of the Volta Basin, West Africa - Bharati, Luna; Eriyagama, Nishadi (2008)
Water allocation to cities, industries and agriculture is a common part of river basin management. However, allocation of water to the environment is receiving progressively more recognition. The term environmental flows is generally used to refer to a flow regime designed to maintain a river in some agreed ecological condition. This report examines a desktop hydrology-based environmental flow assessment method and it's applicability in river basin management. The method and its corresponding software package are first described. This is followed by a case study from Volta River Basin, Ghana, where this method was used to calculate environmental flows. The environmental flows calculations are being proposed to be integrated into the water allocation framework, which is being developed under the Glowa Volta Project.